Three Mechanisms in One Material: Uranium Capture by a Polyoxometalate–Organic Framework through Combined Complexation, Chemical Reduction, and Photocatalytic Reduction. (25th September 2019) - Zhang, Hailong; Liu, Wei; Li, Ao; Zhang, Duo; Li, Xiaoyan; Zhai, Fuwan; Chen, Lanhua; Chen, Long; Wang, Yanlong; Wang, Shuao
Abstract: The design and synthesis of uranium sorbent materials with high uptake efficiency, capacity and selectivity, as well as excellent hydrolytic stability and radiation resistance remains a challenge. Herein, a polyoxometalate (POM)–organic framework material (SCU‐19 ) with a rare inclined polycatenation structure was designed, synthesized through a solvothermal method, and tested for uranium separation. Under dark conditions, SCU‐19 can efficiently capture uranium through ligand complexation using its exposed oxo atoms and partial chemical reduction from U VI to U IV by the low‐valent Mo atoms in the POM. An additional U VI photocatalytic reduction mechanism can occur under visible light irradiation, leading to a higher uranium removal without saturation and faster sorption kinetics.SCU‐19 is the only uranium sorbent material with three distinct sorption mechanisms, as further demonstrated by X‐ray photoelectron spectroscopy (XPS) and X‐ray absorption near edge structure (XANES) analysis. Abstract : Das Einfangen von Uran durch ein Polyoxometallat‐organisches Gerüst ist über drei Mechanismen möglich: Komplexierung, chemische Reduktion und photokatalytische Reduktion. Das Material hat eine einzigartige 2D+2D→3D‐Polykatenationstruktur, was zu ausgezeichneter Stabilität gegenüber Hydrolyse und Ionisierungsstrahlung führt.